Лямбда-@ tg@/1+ctg +ctg@/1+tg@ = tg@ + ctg @ - 1
Лямбда-@
tg@/1+ctg +ctg@/1+tg@ = tg@ + ctg @ - 1
Ответ(ы) на вопрос:
[latex] \frac{tg \alpha }{1+ctg \alpha } + \frac{ctg \alpha }{1+tg \alpha } = \frac{sin \alpha }{cos \alpha (1+ \frac{cos \alpha }{sin \alpha } )} + \frac{cos \alpha }{sin \alpha (1+ \frac{sin \alpha }{cos \alpha })} =\\\\= \frac{sin^2 \alpha }{cos \alpha (sin \alpha +cos \alpha )} + \frac{cos^2 \alpha }{sin \alpha (cos \alpha +sin \alpha )} =\\\\= \frac{sin^3 \alpha +cos^3 \alpha }{sin \alpha \cdot cos \alpha \cdot(sin \alpha +cos \alpha )} =[/latex]
[latex]= \frac{(sin \alpha +cos \alpha )(sin^2 \alpha -sin \alpha \cdot cos \alpha +cos^2 \alpha )}{sin \alpha \cdot cos \alpha (sin \alpha +cos \alpha )} =[/latex]
[latex]= \frac{sin^2 \alpha }{sin \alpha \cdot cos \alpha } - \frac{sin \alpha \cdot cos \alpha }{sin \alpha \cdot cos \alpha } + \frac{cos^2 \alpha }{sin \alpha \cdot cos \alpha } =tg \alpha -1+ctg \alpha [/latex]
Не нашли ответ?
Похожие вопросы